Charge transfer-resistance in nitrogen-doped/undoped graphene: Its influence on the electro-catalytic reduction of H2O2. (1st December 2016) - Magerusan, Lidia; Pogacean, Florina; Socaci, Crina; Coros, Maria; Rosu, Marcela-Corina; Pruneanu, Stela
Abstract: Nitrogen doped (N-Gr) and undoped (TRGO) graphene were chemically synthesized and characterized by TEM, STEM-EDX and XPS. The electrochemical reduction of H2 O2 was investigated with bare glassy carbon (GC) electrode and with GC modified with each graphene sample. The active area of TRGO/GC and N-Gr/GC modified electrodes were found to be 0.75 and 0.295 cm 2, respectively. Both were considerably larger than that of bare GC (0.07 cm 2 ). We carefully looked at the kinetic of interfacial electron transfer process and found that the charge-transfer resistance (Rct ) of TRGO/GC electrode (7.83 × 10 6 Ω) was significantly lower than that of N-Gr/GC electrode (4.81 × 10 7 Ω) or bare GC (1.74 × 10 9 Ω). Interestingly, although TRGO/GC electrode had the largest active area and the smallest charge transfer resistance, it did not promote the H2 O2 electrochemical reduction. In contrast, N-Gr/GC modified electrode exhibited an enhanced electro-catalytic activity towards H2 O2 reduction, which was related to the presence of heterogeneous atoms into the sp 2 carbon network.